Questions of Pedagogy in the Works of Professor k. Zhubanov - Elizavetta I. Isibaeva, Zhaidarman A. Ganibaeva, Salima S. Seitenova , Makpal K. Zhazykova, Gulim Y. Yeleussinova, (Opción, 2019)
The purpose of our research consists in the historical and functional analysis of the works of Professor K. Zhubanov and identification of his views on the modern development of pedagogy and psychology. As a result, the main support of the language communication question, widely developed at the end of the XX century, is communicative content and value of the speech between people and ethnoses. In conclusion, it is possible to note that origins of pedagogical heritage of Professor K. Zhubanov are progressive ideas of the Kazakh thinkers.